CRISPR/Cas9 Gene Therapy Innovation: Targeting HPV16 Oncogene Gene for Cervical Cancer Prevention - Muhammad Rafi Pratama Shidiq; Aghniya Nur Rizka Fadila; Alifah Mustari (Indonesian Journal of Engineering and Technological Innovation, 2025)
Human Papillomavirus (HPV) is a causative agent of cervical cancer. Approximately 60% of cervical cancers are caused by the infection of HPV-16. Cervical cancer is the second most common cancer affecting women. Various treatments and therapies are being explored to treat cervical cancer, but there is still a need for safer, more effective, and affordable technologies. CRISPR-Cas9 is a modern biotechnology technology derived from bacterial immune mechanisms to combat viruses and phages. This mechanism can be applied as a therapeutic medium, as it allows for specific and precise genome editing. The aim of this literature review is to determine the potential and effectiveness of CRISPR-Cas9 as a therapeutic agent for cervical cancer. The method used involves a literature study, based on searches on official websites such as Pubmed, Google Scholar, and other official journals with the keywords “CRISPR-Cas9” and “Cervical Cancer.” The results indicate that CRISPR can target the Cas9 protein to deactivate the oncogenes E6 and E7 in HPV-16, thereby promoting cell cycle arrest and apoptosis. Various studies have been developed to improve the side effects associated with CRISPR-Cas9. However, research on CRISPR-Cas9 has shown a reduction in cancer tissue and increased apoptosis. This method is effective for cancer treatment and needs further investigation to reduce the incidence of cervical cancer.